Enhanced stretchability of metal/interlayer/metal hybrid electrode. Issue 8 (18th February 2021) - Han, Seungseok; Seo, Ki-Won; Kim, Wansun; Kim, Taek-Soo; Lee, Jung-Yong
Abstract : Stretchable hybrid electrodes utilizing grain size engineering and hybridization with conductive interlayers are proposed. The conductive interlayers in the hybrid structure affect the crack formation and propagation significantly. Abstract : Despite the excellent electrical conductivity of metal thin film electrodes, their poor mechanical stretchability makes it extremely difficult to apply them as stretchable interconnect electrodes. Thus, we propose a novel stretchable hybrid electrode (SHE) by adopting two strategies to overcome the metal thin film electrode limitations: grain size engineering and hybridization with conductive interlayers. The grain size engineering technique improves the inherent metal thin film stretchability according to the Hall–Petch theory, and the hybridization of the conductive interlayer materials, poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) and carbon nanotube (CNT), suppresses crack propagation. Especially, the CNT-inserted SHE exhibits a decreased resistance change of approximately 32% in tensile test and 75% in a 10 000 cycle fatigue test because of the rough surface of the designed electrode, which relieves maximum stress by redistributing it more evenly to prevent penetrating crack propagation.